Introduction to kinesiology studying physical activity - Hoffman, Shirl J. 1939-; Knudson, Duane V. 1961- (Human Kinetics, 2018)
Aimed at undergraduate students in sport and exercise science courses, this text provides a comprehensive, reader-friendly overview of sports science, laying a solid foundation for future learning and for working as a professional in any field relating to physical activity.